Characterization of Vimentin-Immunoreactive Astrocytes in the Human Brain - O’Leary, Liam Anuj; Davoli, Maria Antonietta; Belliveau, Claudia; Tanti, Arnaud; Ma, Jie Christopher; Farmer, William Todd; Turecki, Gustavo; Murai, Keith Kazuo; Mechawar, Naguib (Frontiers in Neuroanatomy, 2020)
Astrocytes are commonly identified by their expression of the intermediate filament protein glial fibrillary acidic protein (GFAP). GFAP-immunoreactive (GFAP-IR) astrocytes exhibit regional heterogeneity in density and morphology in mouse brain as well as morphological diversity in human cortex. However, regional variations in astrocyte distribution and morphology remains to be assessed comprehensively. This was the overarching objective of this post-mortem study, which mainly exploited the immunolabeling of vimentin (VIM), an intermediate filament protein expressed by astrocytes and endothelial cells which presents the advantage of labelling cell structures more extensively. We compared the densities of VIM-IR and GFAP-IR astrocytes in various brain regions (prefrontal and primary visual cortex, caudate nucleus, mediodorsal thalamus) from individuals having died in the absence of neurological or psychiatric conditions. The morphometric properties of VIM-IR in these brain regions were also assessed. We found VIM-IR astrocytes generally express the canonical astrocytic markers Aldh1L1 and GFAP but that VIM-IR astrocytes are less abundant than GFAP-IR astrocytes in all human brain regions, particularly in the thalamus, where VIM-IR cells were nearly absent. About 20% of all VIM-IR astrocytes presented a twin cell morphology, a phenomenon rarely observed for GFAP-IR cell. Furthermore VIM-IR astrocytes in the striatum were often seen to extend numerous parallel processes which seemed to give rise to large VIM-IR fiber bundles projecting over long distances. Moreover, morphometric analyses revealed that VIM-IR astrocytes were more complex than their mouse counterparts in functionally homologous brain regions, as has been previously reported for GFAP-IR astrocytes. Lastly, the density of GFAP-IR astrocytes in grey and white matter were inversely correlated with vascular density, but for VIM-IR astrocytes this was only the case in grey matter, suggesting that gliovascular interactions may especially influence the regional heterogeneity of GFAP-IR astrocytes. Taken together, these findings reveal special features displayed uniquely by human VIM-IR astrocytes and illustrate that astrocytes display important region- and marker-specific differences in the healthy human brain.